Physical and Chemical Barriers in Root Tissues Contribute to Quantitative Resistance to Fusarium oxysporum f. sp. pisi in Pea - Bani, Moustafa; Pérez-De-Luque, Alejandro; Rubiales, Diego; Rispail, Nicolas (Frontiers in Plant Science, 2018)
Fusarium wilt caused by Fusarium oxysporum f. sp. pisi (Fop) is one of the most destructive diseases of pea worldwide. Control of this disease is difficult and it is mainly based on the use of resistant cultivars. While monogenic resistance has been successfully used in the field, it is at risk of breakdown by the constant evolution of the pathogen. New sources of quantitative resistance have been recently identified from a wild relative Pisum spp. collection. Here, we characterize histologically the resistance mechanisms occurring in these sources of quantitative. Detailed comparison, of the reaction at cellular level, of eight pea accessions with differential responses to Fop race 2, showed that resistant accessions established several barriers at the epidermis, exodermis, cortex, endodermis and vascular stele efficiently impeding fungal progression. The main components of these different barriers were carbohydrates and phenolic compounds including lignin. We found that these barriers were mainly based on three defence mechanisms including cell wall strengthening, formation of papilla-like structures at penetration sites and accumulation of different substances within and between cells. These defence reactions varied in intensity and localization between resistant accessions. Our results also clarify some steps of the infection process of F. oxysporum in plant and support the important role of cell wall-degrading enzymes in F. oxysporum pathogenicity.